"The Answer My Friend is Blowin' in the Wind": A stochastic assessment of wind farms financial feasibility and economic efficiency. (December 2021) - Kumar, Indraneel; Tyner, Wallace E.; Labi, Samuel; Sinha, Kumares C.
Abstract: Two financial incentives that have spurred the growth of renewable energy including wind farms are Production Tax Credits (PTC) and Property Tax Abatement (PTA). PTC provides a tax credit of 1¢–2¢ per kilowatt-hour for the first 10 years of electricity generation for utility-scale wind, and PTA is a rebate provided by the local governments to wind farms in the U.S. Midwestern states. Past researches suggest that the breaking-even of renewable energy projects can partly be attributed to PTC. However, in cognizance of the irregular availability of such incentives, there seems to exist a need for financial feasibility analysis of the wind farms. The study uses a stochastic method and a scenario approach to address this research question. The analysis considers the capital and operating costs, interest payments, local and federal taxes, and production of wind energy and sales revenues, and inherent uncertainties in key parameters. The results shed some light on the impacts of PTC and PTA on the financial feasibility of wind farms in the U.S. Midwestern states. It is observed that PTC is a more effective instrument compared to PTA. The paper concludes by discussing policy implications of local government rebates and federal incentives. Highlights: The study analyzes the stochastic economic and financial feasibility of wind farms. Life-cycle impacts of federal and local incentives and rebates are simulated. Production Tax Credits are effective for the breaking-even of the wind farms. Wind farms can be self-sustaining without rebates such as Property Tax Abatements.